Investigation of the occurrence of mycotoxins in staple foods consumed in Kinshasa (DRC) by an LC-MS/MS-based multimycotoxin analytical approach - Michel Kawayidiko Kasongo; Arthur Mpanzu Duki; Jérémie Kindenge Mbinze; Patrick B. Memvanga; Christophe Tsobo Masiala; Sarah De Saeger; José Diana Di Mavungu (Orapuh, Inc., 2024)
Introduction Mycotoxins are harmful contaminants for human and animal health; their presence also impacts crop production and economies worldwide. They are frequently present in various African staple foods. Purpose In this study, a multi-mycotoxin analysis approach was implemented to reveal mycotoxin contamination of important staple foods in Kinshasa (Democratic Republic of the Congo). Methods A multi-mycotoxin analysis approach based on liquid chromatography tandem mass spectrometry (LC-MS/MS) with electrospray interface operated in positive mode (ESI+) and quadrupole mass analyzer was used. Twenty-five mycotoxins were investigated in 18 samples of staple foods collected in different markets in Kinshasa city, including maize flour (n=8), cassava flour (n=5), and peanut paste (n=5). Results Twenty mycotoxins were present in these samples at quantifiable levels. The maize flour samples were the most contaminated with aflatoxin B1 (AFB1) (87.5%), total aflatoxin (AFT) (100%), fumonisin B1 (FB1) (87.5%), deoxynivalenol (DON) (75%), and nivalenol (NIV) (75%). Emerging mycotoxins such as beauvericin (BEA), enniatin B (ENN B), alternariol (AOH), and alternariol mono-methyl ether (AME) were more frequent in maize flour. The study found that 25% of maize flour and 20% of peanut paste samples exceeded the European Commission's regulatory limits for aflatoxin B1 (AFB1) and total aflatoxins (AFT). Additionally, ochratoxin A (OTA) was detected in one maize sample at a concentration above the regulatory limit. This could expose consumers to their genotoxic, teratogenic, and immunosuppressive effects. As for OTA, there are fears of its harmful effects, including nephrotoxicity and mutagenicity. The aflatoxin/fumonisin (AF/F) combination was more frequently observed (50% of all samples) than AF/DON, DON/F, and AF/OTA combinations. Conclusion Data from this exploratory study highlight a possible health risk for the population of Kinshasa through the consumption of maize flour, as well as the need for continuous monitoring of mycotoxins in this staple food that is increasingly being consumed across the Democratic Republic of the Congo.